Marital Flourishing: Kualitas Perkawinan dalam Teori Eudaimonik - Siti Rohmah Nurhayati; Avin Fadilla Helmi (Buletin Psikologi, 2013)
Marital quality has been described in various concepts. One of them is marital flourishing suggested by Fowers and Owenz (2010). This article presents the concept of marital flouris hing and eudaimonic theory that emerged from Aristotle's view about happiness. Maritalflourishing in this article is assessed by two dimensions of marital quality.First the goal di mension that divides instrumental goals and constitutive goals.Second the goal pursuit that distinguish marital flourishing between individual goal pursuit and shared goal pursuit. Marital flourishing as the highest quality of marriage is characterized by the height of communal activity between couple and the height of constitutive goals. Other types of marital quality and the forms of activity that characterize marital flourishing is also described further in this article.